Why Government Fails So Often - PETER H. SCHUCK (Princeton University Press, 2014)
Our political system has long been admired and wondered at by Americans and outsiders who marvel at its ability to govern for 225 years a remarkably dynamic, diverse society. Yet most Americans today believe that our government is failing to deliver what it promises, and they have lost confidence in its effectiveness. Herein lies a deep and dangerous dilemma, one that this book seeks to explain and perhaps to help solve. Consider some of our governmentâ€™s past successesâ€”many of commission, some of restraint. Since the Civil War, the U.S. political system has been extraordinarily stable and durable, experiencing no deep crisis of regime legitimacy and requiring only a dozen additional amendments to our eighteenth-century Constitution, most of them of only historical significance. Our polity and civil society have accepted and integrated a vast number of immigrants of diverse races, religions, languages, and cultural backgrounds, most with relatively low education levels, transforming them into patriotic Americans and loyal permanent residents. Our competitive, resilient economy leads the world in technological innovation and has given us the highest standard of living in the world. (Despite recent setbacks, it still vies for that distinction with oil-rich Norway and tiny tax haven Luxembourg.1) Having rescued our allies in two world wars, the United States has exerted hegemonic military, cultural, diplomatic, and economic power (for better and worse) for seven decades. It has extended civil rights for racial and religious minorities, women, gay people, and the disabled. It reduced poverty significantly between 1960 and 2010, with much of that decline occurring since 1980.2 Its civil society is the worldâ€™s most robust and creative, with a vibrant religious and civic culture that supports a bewildering variety of philanthropic, religious, and social service activities. Among liberal democracies, Americans are by far the most patriotic people; almost 90 percent completely or mostly agree with the statement â€œI am very patrioticâ€; most claim to engage in patriotic activities.3 Our natural environment, highlighted in its national park system and vast tracts of unsettled territory, is stunning.